Navigation-Assisted Total Knee Arthroplasty for Osteoarthritis with Extra-Articular Femoral Deformity and/or Retained Hardware - Daisuke Hamada; Hiroshi Egawa; Tomohiro Goto; Tomoya Takasago; Michihiro Takai; Tetsuya Hirano; Yoshiteru Kawasaki; Natsuo Yasui (Case Reports in Orthopedics)
Total knee arthroplasty (TKA) for osteoarthritis (OA) patients with extra-articular deformity is still challenging because angular deformity, canal sclerosis, or the retained hardware that precludes the use of the traditional intramedullary guide. In addition, atypical bone cut for intra-articular correction leads to imbalanced soft tissue gap. Furthermore, corrective osteotomy should be considered for severe deformity or para-articular deformity cases. Recently, navigation-assisted TKA has been reported to increase the accuracy of prosthetic positioning and limb alignment. This system can calculate mechanical axis regardless of extra-articular deformity, canal sclerosis, or retained hardware. Accordingly, navigation surgery has been considered to be a powerful option especially in TKAs with extra-articular deformity cases. Here, we report 3 successful navigation-assisted TKAs for osteoarthritis with extra-articular deformities and/or retained hardware. Navigation-assisted TKA is an effective and reliable alternative for patients with extra-articular deformities.